PENGARUH KESADARAN, TINGKAT PEMAHAMAN, TINGKAT PENDAPATAN DAN LINGKUNGAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DIMASA PANDEMI COVID-19 DI KECAMATAN KALASAN - Eni Dwi Susliyanti, S.E., M.Si; Alief Indita Agustiyani (Jurnal Solusi, 2022)
This research aims to examine the effect of taxpayer awareness, level of understanding of taxpayers, tax environment and income level of taxpayers on compliance in paying Land and Building Taxes during the COVID-19 pandemic in Kalasan District. This type of research is quantitative research using primary data sources obtained directly from respondents through questionnaires. The data analysis method used in this research is multiple linear regression test. The results showed that: 1) Awareness has a significant positive effect on taxpayer compliance in paying Land and Building Tax. 2) The level of understanding has a significant 3) The level of income has a possitif effect but not significant on taxpayer compliance in paying Land and Building Tax 4) Tax environment has a significant positive effect on taxpayer compliance in paying Land and Building Tax.5) Simultaneously awareness, level of understanding, income level of taxpayers and tax environment affect compliance in paying Land and Building Tax 5)Based on the results of the R2 test, it is known that the Adjusted R Square value is 0.35 so that the contribution between taxpayer awareness, taxpayer understanding level, taxpayer income level and tax environment is 35% so that the remaining 65% is influenced by other factors outside of this research